Nanoparticles from Equine Fetal Bone Marrow-Derived Cells Enhance the Survival of Injured Chondrocytes - Ki Hoon Kim; Tae Sub Park; Byung-Wook Cho; Tae Min Kim (Animals, 2020)
Recent studies have shown that mesenchymal stem cells (MSCs) can play a restorative role against degenerative joint diseases in horses. The purpose of this study was to investigate whether fetal bone marrow-derived cells (BMC)-derived nanoparticles (BMC-NPs) can stimulate the survival of equine chondrocytes. Equine fetal BMCs were isolated and characterized, and the role of BMC-NPs s in equine chondrocytes undergoing inflammatory cell death was examined. BMCs have several characteristics, such as the potential to differentiate into chondrocytes and osteocytes. Additionally, BMCs expressed immunoregulatory genes in response to treatment with tumor necrosis factor-alpha (TNF-α) and Interleukin 1 beta (IL-1β). We found that BMC-NPs were taken up by equine chondrocytes. Functionally, BMC-NPs promoted the growth of chondrocytes, and reduced apoptosis induced by inflammatory cytokines. Furthermore, we observed that BMC-NPs upregulated the phosphorylation of protein kinase B (Akt) in the presence of IL-1β, and reduced the phosphorylation of TNF-α-induced activation of extracellular signal-regulated kinase 1/2 (ERK1/2) in the chondrocytes. Cumulatively, our study demonstrated that equine fetal BMC-NPs have the potential to stimulate the survival of chondrocytes damaged by inflammatory cytokines. Thus, BMC-NPs may become an alternative cell-free allogenic therapeutic for degenerative joint diseases in horses.